2022
DOI: 10.3390/molecules27175707
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-Phosphinoarenesulfonamide-Mediated Staudinger Reduction of Aryl and Alkyl Azides

Abstract: Conventional Staudinger reductions of organic azides are sluggish with aryl or bulky aliphatic azides. In addition, Staudinger reduction usually requires a large excess of water to promote the decomposition of the aza-ylide intermediate into phosphine oxide and amine products. To overcome the challenges above, we designed a novel triaryl phosphine reagent 2c with an ortho-SO2NH2 substituent. Herein, we report that such phosphine reagents are able to mediate the Staudinger reduction of both aryl and alkyl azide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Our studies were initially inspired by pioneering works [7] on the stabilization of penta‐coordinated P(V) species and the annulation strategy [8] we recently developed. We have demonstrated that B‐TAP heterocycles have increased stability over uncyclized P(V) aza‐ylides [8] and thereby can serve as a driving force for Staudinger reduction [9] . We speculated that such a framework might enhance the stability of penta‐coordinated P(V) compounds as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies were initially inspired by pioneering works [7] on the stabilization of penta‐coordinated P(V) species and the annulation strategy [8] we recently developed. We have demonstrated that B‐TAP heterocycles have increased stability over uncyclized P(V) aza‐ylides [8] and thereby can serve as a driving force for Staudinger reduction [9] . We speculated that such a framework might enhance the stability of penta‐coordinated P(V) compounds as well.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that B-TAP heterocycles have increased stability over uncyclized P(V) aza-ylides [8] and thereby can serve as a driving force for Staudinger reduction. [9] We speculated that such a framework might enhance the stability of penta-coordinated P(V) compounds as well. Specifically, we proposed that the annulation of orthophosphinoarenesulfonyl fluoride with ortho-azidophenols would construct an unprecedented [5,5,0]-bicyclic P(V) scaffold with the aid of a silicon additive (Scheme 1, d).…”
Section: Resultsmentioning
confidence: 99%
“…From the view of the functionalization of the organic azide, [16] all three nitrogen atoms in trimethylsilyl azide were excluded during the annulation, and trimethylsilyl fluoride was formed. This result was intriguing to us since the conventional Staudinger reaction predominately followed the pathway where two nitrogen atoms were excluded from the azide [14a,15b] . We proposed that multiple nitrogen atom exclusion modes could be reached by a single organophosphorus reagent if its reactivity could be tuned by additional reagents or catalysts.…”
Section: Resultsmentioning
confidence: 99%